A pro-poor approach to planning public open spaces as tourism commons the case of the municipality of Pagudpud, Ilocos Norte, Philippines - Malinao, Jennifer Carisma (School of Urban and Regional Planning, University of the Philippines Diliman, 2011)
Set against the backdrop of the third world where increasing poverty remains a reality, the study sought to explore the nature of use and the characteristics of users of open spaces in the Philippines within the context of their 'public' and 'social' character - contested spaces where the citizens, especially the poor, can claim their rights to these spaces. Further, while various studies have been conducted linking together tourism and poverty, as well as public spaces and poverty, this study attempted to build and test a theory linking together tourism, public open spaces and poverty. By looking at the specific case of the vast public open spaces of an emerging tourism destination in the northern region of the Philippines - the Municipality of Pagudpud, the study revealed that the lower income people are the dominant users of public open spaces of Pagudpud. This is especially manigest in those elements of the public open space that comprise the urban structure: the plaza; and the streets, sidewalks and edge spaces. For the shoreline open spaces or public beaches, there is an observed mix of dominant users: both the lower income locals who earn a living from tourism and fishing, and the middle to upper income class tourists who come for recreation and relaxation. The dominant role of public open spaces in Pagudpud is still social, except for the streets and sidewalks that host more economic uses as spaces for people to earn a living. Building on the convergence of evidences coming from four (4) various sources - survey, key informant interviews, direct observations and documentations, the results further validated the theoretical proposition that the locality's public open spaces have vast potentials to be developed as tourism commons - natural and built attractions, facilities or infrastructure that are shared in common by both the locals and tourists alike, where the local people can benefit much from the gains of pro-poor and community-based sustainable tourism development. Building on the findings of the dominant users and uses of public open spaces, a needs assessment was further conducted using levels of population, poverty and accessibility as indicators in a GIS-based weighted criteria ranking tool. The result of the needs assessment became the basis for conceptualizing the proposed spatial and policy frameworks for a pro-poor approach to planning and designing public open spaces. The conceptualization of the proposed spatial framework involved the plotting of Pagudpud's Green Infrastructure Network; and the establishment of a hierarchy of its existing and proposed central, secondary, community and neighborhood open spaces considering the needs of the lower income users. Finally, the study concludes that, indeed, public open spaces are key elements in the livelihoods of the poor, particularly in advancing the informal street economy as a strategy for poverty reduction. Planners and decision-makers need only to be creative on how to accommodate the informal economy in these public open spaces - especially in staging community-based tourism activities - hence, improve the spaces of the poor.